Visi dan Misi Undang-Undang Guru dan Dosen (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This article looks at the goals and purpose of Law Number 14 of 2005, which is about teachers and lecturers, and how this law can help improve the education system in Indonesia. The study uses a qualitative method, which means it looks at information from books and other documents, as well as research papers related to this topic. The results show that this law recognizes teachers and lecturers as professional people with clear standards for their skills, their rights, what they are expected to do, and the legal support they should get. Policies like teacher certification and ongoing training have helped make teachers' jobs better and more respected. But there are still some problems, like uneven application of the law in different areas, too much paperwork, and not enough improvement in how well students are learning. So, it’s important to keep checking how well these policies are working and to make sure they are carried out properly, so that the law’s goals can help education in Indonesia improve in a lasting way.